Analisis Keaktifan Belajar Siswa melalui Model Project Based Learning dalam Pembelajaran IPA - Aditama, Dhavi Yoga; Bella, Aisyatum; Kamilah, Arina; agustin, nurhaningtyas (Tarunateach: Journal of Elementary School, 2024)
This study aims to analyze student activeness in science learning at MI Plus Wildan Assyifa using the Project Based Learning (PjBL) model. The focus is to obtain in-depth information about the level of student activeness as a reference for teachers, as well as to offer updates from previous studies that rarely highlight aspects of student activeness specifically. The research method used is qualitative with a narrative approach. Qualitative research emphasizes the quality and meaning behind the phenomenon, while the narrative approach is used to tell individual or group experiences through documentation and personal analysis. The results of the study showed a significant increase in student activeness after the implementation of PjBL integrated with the simulation method. Measurement of activeness was carried out through observation, interviews, and documentation, which included the stages of planning, implementation, observation, and reflection. Students showed active involvement in preparing project schedules, bringing materials, and collaborating in working on the volcanic eruption simulation task. The teacher managed to overcome the challenges of attracting students' attention and limited facilities with creativity and the use of simple materials, without complaints from parents. This method not only improves understanding of the material, but also forms student character such as responsibility, discipline, self-confidence, and curiosity. Students become more enthusiastic, interactive, and able to overcome learning boredom. Teachers feel motivated to see the positive responses of students and consider this method to have a broad impact on the science learning process, creating a more lively and dynamic classroom atmosphere.